Effect of Combined Oral Contraception on Coagulation Profiles in Women Attending Fertility Control Clinic in Baqubah City- Iraq - Salman, Sawsan T.; Hussein, Areej A.; Saadi, Raakad K. (Journal of the Faculty of Medicine Baghdad, 2018)
Background: Use of oral contraception has been associated with an increased abnormalities of lipid and carbohydrate metabolism as well as hemostatic variables at baseline (increased plasma levels of factor VII, factor X, fibrinogen and of D-dimers). Objectives: To evaluate the effect of oral contraceptive pills (combined pills) on coagulation tests,prothrombin time (PT), activated partial thromboplastin time (APTT), and fibrinogen level. Patients and methods: This is a descriptive cross sectional study which was conducted in fertility control clinic in Al-Batool Teaching Hospital for Maternity and Children in Baqubah city, during the period from December 2015 to October 2016. Eighty eight women were enrolled in this study according to inclusion criteria, 63 women were use contraceptive pills(study group) and other 25 females not taken these pills (control group), prothrombin time, activated partial thromboplastin time and fibrinogen level measured by using the coagulometer instrument. Results: The mean age was 29.89 and 30.89 years for all participants (subject and control) it was (range 20-45). The results of cases revealed that PT= 12.89 seconds, APTT= 30.45 seconds, and fibrinogen level= 2.18 g/l while the results of control group revealed that PT= 11.92 seconds, APTT= 29.85 seconds and fibrinogen level= 2.24 g/l. Overall no significant variations were noticed in these parameters with P value > 0.05 also no significant changes were noticed between age groups, duration of oral contraceptives and some clinical parameters. Conclusion: Effect of combined oral contraceptives use on prothrombin time, activated partial thromboplastin time and fibrinogen levels are minor compared with control group.